Shakespeare's theatre - Hodges, C. Walter (Cyril Walter), 1909- (London : Oxford University Press, 1972)
Examines how the pagan festivals and religious dramas performed throughout England evolved into the professional theaters, such as the Globe, in London.
Includes index.
Keywords: Shakespeare, William, -- 1564 - 1616 -- Stage history -- To 1625 -- Juvenile literature; Theater -- England -- History -- Juvenile literature